Raising Healthy Children: Age Four - Kate Bennett; Gail Kauwell; Karla P. Shelnutt (EDIS, 2017)
As children continue their preschool years, they learn many new things and develop their own opinions and ideas. During this time, people inside and outside of the home may greatly influence them. As preschoolers continue to learn and grow, caregivers can take many steps to guide their children in a healthy and positive direction. This 3-page fact sheet is a minor revision written by Kate Bennett, Gail Kauwell, and Karla P. Shelnutt, and published by the Department of Family, Youth and Community Sciences, April 2017.